Persistent miller fisher syndrome following COVID-19 infection: A case report - Margaret Donat; Ivie Odiase; Aldo Alleva; Aditya A. Bissoonauth; Hamnah Khan; Sara Siddiqui (Journal of Family Medicine and Primary Care)
Guillain-Barré syndrome (GBS) is an inflammatory disease of the peripheral nervous system, with Miller-Fisher syndrome (MFS) being a rare variant. Recent studies have shown GBS and MFS to be a common side effect of COVID-19. This case report highlights the clinical presentation of a patient diagnosed with post-COVID-19 MFS, their subsequent treatment challenges, and the prognostic outcomes, contributing to the limited scientific literature of this uncommon affliction. A comprehensive case report of a 57-year-old man with significant medical history was conducted to determine the appropriate diagnosis based on the perceived symptoms following COVID-19. Per the Northwell health human research protection program, the publication of case reports involving up to three patients is not considered human-subject research and does not require IRB review and approval. Our patient was diagnosed with MFS, making him the longest-known adult with COVID-19-associated MFS without resolution of neurologic symptoms after intravenous immunoglobulin (IVIG) dose administration. Our case report posits the first-known patient to have a more severe form of MFS or resistance to IVIG dose. The current study also highlights the association between COVID-19 and MFS, warranting the need for more studies to understand the disease pathophysiology and new biomarkers for targeted treatments.